Research progress and key technologies of intelligent monorail cranes in coal mines - MA Hongwei; DUAN Youyou; XUE Xusheng; SUN Siya; ZHANG Ye; WANG Chuanwei; GUO Yifeng; CUI Wenda (Gong-kuang zidonghua, 2023)
The advantages and disadvantages of five commonly used mining monorail cranes, namely explosion-proof diesel engine monorail crane, explosion-proof battery monorail crane, pneumatic monorail crane, rope traction monorail crane, and cable dragging monorail crane, are analyzed. It is pointed out that explosion-proof diesel engine monorail crane and explosion-proof battery monorail crane have been widely used for underground equipment and material transportation in coal mines due to their strong transportation capacity. The explosion-proof battery monorail crane has green and clean features. It has gradually become a key research and development equipment for underground auxiliary transportation in coal mines. This paper analyzes the research status of the mining monorail crane system from four aspects of battery drive, positioning, measurement and control, and information transmission. It is pointed out that the current mining monorail crane system has low automation and intelligence levels. To achieve intelligent transportation of the monorail crane, it is necessary to study the key technologies such as lithium battery explosion-proof and battery management of the monorail crane, global and local fusion precise positioning, multi-sensor information fusion intelligent measurement and control, edge computing information transmission, etc. For the explosion-proof and battery management technology of lithium battery, a topology optimization design method of explosion-proof large capacity lithium battery structure based on variable density method, and a balanced management scheme based on improved sparrow search algorithm/genetic algorithm are proposed. For precise positioning technology, a global positioning method based on inertial navigation and odometer fusion, and a local positioning method based on visual+UWB combination are proposed. For intelligent measurement and control technology, an intelligent detection method based on recursive least squares algorithm/second-order approximate extended Kalman filter , the real-time construction method for follow-up electronic fences, and vector control method based on fuzzy rules are proposed. For the information transmission technology, the 'local-short range-ground' communication system architecture based on the fusion of 5G network and the distributed data calculation and transmission method based on edge computing are proposed. The proposal of key technical issues and solutions for intelligent monorail cranes in coal mines provides a new approach to accelerate the development of intelligent monorail cranes in coal mines.